Cover Image, Volume 26, Issue 8. (23rd July 2018) - Kuhn, Pascal; Nouri, Bijan; Wilbert, Stefan; Prahl, Christoph; Kozonek, Nora; Schmidt, Thomas; Yasser, Zeyad; Ramirez, Lourdes; Zarzalejo, Luis; Meyer, Angela; Vuilleumier, Laurent; Heinemann, Detlev; et al.
Abstract : The cover image, by Pascal Kuhn et al., is based on the Special Issue Paper Validation of an all‐sky imager–based nowcasting system for industrial PV plants, https://doi.org/10.1002/pip.2968 .